IL-1beta mediates MMP secretion and IL-1beta neosynthesis via upregulation of p22phox and NOX4 activity in human articular chondrocytes. Issue 11 (November 2015) - Rousset, F.; Hazane-Puch, F.; Pinosa, C.; Nguyen, M.V.C.; Grange, L.; Soldini, A.; Rubens-Duval, B.; Dupuy, C.; Morel, F.; Lardy, B.
Summary: Objectives: Osteoarthritis (OA) is characterized by a progressive alteration of the biochemical properties of the articular cartilage. Inflammation plays a major role in OA, particularly through the cytokine Interleukine-1β, promoting reactive oxygen species (ROS) generation and matrix metalloproteinases (MMP) synthesis by the chondrocytes, orchestrating matrix proteolysis. NADPH oxidases (NOX) are membrane enzymes dedicated to the production of ROS. Role of oxidative stress is well established in OA; however, contribution of NOX in this process is still poorly documented. In this study, we addressed the role of NOX in primary human articular chondrocytes (HAC) upon inflammatory conditions – namely IL-1β and OA. Design: HAC were collected from patients undergoing hip surgery. Chondrocytes were treated with IL-1β and NOX inhibitors Diphenylene Iodonium, GKT136901, Tiron and Heme oxygenase-1 before MMP expression and NOX activity assessment. Finally, NOX4 expression was compared between OA and non OA parts of hip cartilage ( n = 14). Results: This study establishes for the first time in human that NOX4 is the main NOX isoform expressed in chondrocytes. We found a significant upregulation of NOX4 mRNA in OA chondrocytes. Expression of NOX4/p22 phox as well as ROS production is enhanced by IL-1β. On the other hand, the use of NOX4 inhibitors decreased IL-1β-induced collagenase synthesis by chondrocytes. Moreover, our study support the existence of a redox dependant loop sustaining pro-catabolic pathways induced by IL-1β. Conclusions: This study points out NOX4 as a new putative target in OA and suggests that NOX-targeted therapies could be of interest for the causal treatment of the pathology.